Textual Analysis of Conversation Evidence in the Burning Sun Case: A Critical Discourse Analysis of Fairclough’s Model - Zam, Nurul Hikmah Alfilail; Sawirman, Sawirman; Usman, Fajri (Jurnal Bahasa dan Sastra, 2024)
The Burning Sun scandal provides an important opportunity to study the use of language in criminal behavior and its influence on power structures in illegal networks. This research aims to answer the questions: How is language used in conversations related to this scandal to create and sustain criminal behavior? Using critical discourse analysis (CDA) based on Norman Fairclough's framework, this study analyzed conversations related to the case. Conversational evidence was taken from several trusted Korean news portals and categorized by topics such as prostitution, drug use, gambling, and illegal content dissemination. The analysis showed that the criminal group used language that reflected a well-coordinated structure, where various roles were clearly laid out, despite the rigid communication patterns. The use of imperative and interrogative sentences indicates careful planning and efficient interaction. In addition, this study reveals how social expectations and cultural prejudices are utilized, especially in the exploitation of women. In conclusion, this study emphasizes the importance of text analysis in forensic investigations, providing insights into how language reflects criminal activity and power dynamics. The findings support combining linguistic methods with legal procedures to uncover hidden aspects of criminal organizations and improve the efficiency of law enforcement.